2015
DOI: 10.1021/acs.orglett.5b02360
|View full text |Cite
|
Sign up to set email alerts
|

Kadcoccinones A–F, New Biogenetically Related Lanostane-Type Triterpenoids with Diverse Skeletons from Kadsura coccinea

Abstract: Six new lanostane-related triterpenoids, kadcoccinones A-F (1-6), were isolated from Kadsura coccinea. Compound 3 possesses a novel 6/6/9-fused carbocyclic core containing a rare oxabicyclo[4.3.1]decane system. Compounds 4 and 5 are isomers representing the first example of the 18(13 → 12)-abeo-26-norlanostane triterpenoid. The absolute configurations of 1 and 4-6 were defined by X-ray diffraction and experimental ECD spectra, and that of 3 was elucidated by quantum chemical calculations. The plausible biogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 20 publications
(18 reference statements)
2
20
0
Order By: Relevance
“…For the K562, Bel‐7402, and A549 cell lines, Kadlongilactone A‐B and Longipedlactone A showed high cytotoxicity, with IC50 values of 0.1, 0.1, and 1.0 μmol/L, respectively (Gao et al, 2008). Hu et al (2015) has been reported that kadcoccinones A‐F exhibit cytotoxic activity against six cancer cell lines (HL‐60, SMMC7721, A‐549, MCF‐7, SW‐480, and Hela). The treatment of single Xenopus embryo cells with kadsuracoccinic acid A is reported to be capable of detained cleavage of these cells with an IC50 value of 0.32 μg/ml (H. Li, Wang, Miyata, & Kitanaka, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For the K562, Bel‐7402, and A549 cell lines, Kadlongilactone A‐B and Longipedlactone A showed high cytotoxicity, with IC50 values of 0.1, 0.1, and 1.0 μmol/L, respectively (Gao et al, 2008). Hu et al (2015) has been reported that kadcoccinones A‐F exhibit cytotoxic activity against six cancer cell lines (HL‐60, SMMC7721, A‐549, MCF‐7, SW‐480, and Hela). The treatment of single Xenopus embryo cells with kadsuracoccinic acid A is reported to be capable of detained cleavage of these cells with an IC50 value of 0.32 μg/ml (H. Li, Wang, Miyata, & Kitanaka, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Kadsura coccinea was also the source of six new lanostane-related triterpenoids, kadcoccinones A–F. Kadcoccinone C ( 619 ) possessed an unprecedented 6/6/9-fused carbocyclic core containing a rare oxabicyclo[4.3.1]decane system, while kadcoccinones D ( 620 ) and E ( 621 ) were two novel 18(13→12)-abeo-26-norlanostane triterpenoids (Hu et al, 2015 ). Neogenkwanines A–H ( 622 - 629 ), daphnane-type diterpenes with a 4,7- or 4,6-oxo bridge, were isolated from Daphne genkwa (Mianyang, Sichuan, China) (Li et al, 2015c ).…”
Section: Terrestrial Plantsmentioning
confidence: 99%
“…In the last few decades, phytochemical work on the family Schisandraceae has resulted in a seminal contribution to novel structural frameworks for triterpenoidal skeletons [1,2,3,4]. Recently, some promising sesquiterpenes has also been reported from the plants of family Schisandraceae [5,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%